Персоналізовані маркетингові рішення для переробних підприємств молочної галузі - Кукіна, Наталя Володимирівна; Kukina, Natalia; Тесленко, Максим Вікторович (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті досліджено можливості впровадження персоналізованих маркетингових рішень на переробних підприємствах молочної галузі України в умовах цифрової трансформації та зміни споживчої поведінки. Розкрито передумови переходу від масових комунікацій до індивідуальних підходів. Проаналізовано світову практику використання мобільних застосунків, програм лояльності, QR-кодів і гейміфікаційних механізмів у молочній промисловості. Обґрунтовано концепцію мобільного застосунку як інструменту управління клієнтським досвідом, що забезпечує персоналізацію пропозицій, збір поведінкових даних і підвищення лояльності споживачів. Визначено головні напрями цифрової взаємодії та представлено медіаплан, здатний підсилити конкурентоспроможність вітчизняних брендів. /// EN: The article examines the potential of personalised marketing in the operations of dairy processing enterprises in Ukraine under conditions of digital transformation and intensifying market competition. The introduction substantiates the relevance of shifting from traditional communication approaches to personalised models of interaction with consumers, which involve the use of mobile applications, loyalty programmes and digital analytics. It is emphasised that the current environment in which dairy processing enterprises operate requires a revision of marketing strategies, taking into account changes in consumer behaviour, the growing importance of digital communication channels and the need to strengthen long-term consumer engagement. The purpose of the article is to provide a theoretical justification and practical analysis of personalised marketing tools applicable to dairy processing enterprises, as well as to develop a model for implementing a mobile application as an instrument for effective consumer interaction. The main section summarises scientific publications on the development of the dairy market, the digitalisation of marketing activities and the adoption of personalised approaches within enterprise communication policies. The article examines the role of mobile applications as platforms for collecting and processing data on consumer preferences, generating individualised offers, accumulating bonuses and implementing gamification mechanisms. A step-by-step model for the introduction of a mobile application at a dairy processing enterprise is proposed, alongside an algorithm for integrating the producer’s bonus programme with the POS systems of retail chains. It is demonstrated that coordinated interaction among the producer, retailer and consumer within a unified digital ecosystem enhances sales efficiency, increases the accuracy of personalised offers and strengthens customer loyalty. The conclusions highlight that personalised marketing is becoming an essential component of the competitive strategy of dairy processing enterprises. The proposed approach enables the development of long-term consumer relationships, optimises communication processes, and improves marketing performance through the use of digital tools and modern data-processing technologies.
Personalised marketing solutions for dairy processing enterprises
Keywords: персоналізований маркетинг; цифрові комунікації; мобільний застосунок; програма лояльності; QR-коди; гейміфікація; клієнтський досвід; молочна галузь; personalised marketing; digital communications; mobile application; loyalty program; QR codes; gamification; customer experience; dairy industry